(untitled) (Research, Society and Development, 2021)
Agribusiness is the activity that most moves the world economy, not only for the production of food for domestic consumption and export, but also for sustaining other economic sectors. Brazil is the country that stands out the most in this type of activity that has been growing since the last 40 years. The brazilian Agribusiness activity focused on the export market is concentrated, for the most part, on the production of agricultural commodities. Among them, one that has stood out is soybeans, which in 2020 led Brazil to become its largest producer and keeps the country in the ranking of the world’s largest exporter. In view of the great economic importance of this grain for the country and the importance of investigating the possible impacts that financial crises may have on its price, this paper sought to present a study on the possible effects of the 2008 financial crisis (Subprime crisis) in the price of soybean. The daily soybean price data recorded between 07/29/1997 and 12/30/2020 by CEPEA-ESALQ/USP were then analyzed. The Recurrence Plot method and the Recurrence Quantification Analysis were used. The results showed that the Subprime crisis influenced the soybean price dynamics in a way that it started to show a higher degree of predictability in the post-crisis period, suggesting that the market of this commodity was more efficient before the crisis and that the foreign market of soy is more efficient than its domestic one.